2000
DOI: 10.1002/1522-1970(200007/08)2:4<281::aid-jtr228>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Food for tourists?determinants of an image

Abstract: Eating is a physical necessity, but catering services and food image are also very important ingredients of cultural tourism. Food and tourism are increasingly being combined, e.g. in agri‐tourism, wine tours and the sale of food products as souvenirs. However, as this paper illustrates, the development and standards of food for tourists are not determined uniformly by tourism policies, but more significantly by national economic, agricultural and food policies. A comparison between Denmark and Italy illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
136
1
20

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(169 citation statements)
references
References 5 publications
6
136
1
20
Order By: Relevance
“…An exception is food and tourism policies studies, which appear to adopt a national approach (such as Everett & Slocum, 2013;Hjalager & Corigliano, 2000). Similarly, regarding wine tourism studies, many seem to concentrate on specific routes such as wine routes (Bruwer, 2003;Telfer, 2001aTelfer, , 2001b.…”
Section: Food Tourism and Culinary Routesmentioning
confidence: 99%
See 2 more Smart Citations
“…An exception is food and tourism policies studies, which appear to adopt a national approach (such as Everett & Slocum, 2013;Hjalager & Corigliano, 2000). Similarly, regarding wine tourism studies, many seem to concentrate on specific routes such as wine routes (Bruwer, 2003;Telfer, 2001aTelfer, , 2001b.…”
Section: Food Tourism and Culinary Routesmentioning
confidence: 99%
“…This type of initiative is important for food tourism development, although the main objective was not specifically tourism-focused. The primary interest of agriculture and food industries in food tourism is the contribution to an increased awareness of food production, food quality and standards (Hjalager & Corigliano, 2000). Hence, conflicting interests logically occur due to the various priorities and agendas.…”
Section: Food Tourism and Culinary Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing that food experiences are not similar for all individuals, some studies focused on different segments, such as the elderly (Meyer & Conklin, 1998). In earlier studies, Spark, Wildman and Bowen (2000), Neild, Kozak and LeGrys (2000) as well as Hjalanger and Corigliano (2000) found that dining facilities such as restaurants were perceived as important to tourists' overall satisfaction with a destination, and as a significant dimension of the tourism product. However, besides serving excellent food, good service, the location of the restaurant, its decor and intangible aspects such as the ambience and atmosphere were reported to be important factors essential to enhance the dining experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gastronomi turizmine katılan turistler, özel ilgi turizmi kapsamında ele alınabileceği gibi kültür turizmi kapsamında da değerlendirilebilecektir (Hjalager ve Corigliano, 2000). Long'un (2004) bahsi geçen gastronomi turizmi tanımı zamanla, dar kapsamı nedeniyle eleştiri almış ve ardından kavramı açıklamaya yönelik yeni tanımlar türetilmeye başlamıştır.…”
unclassified